Mathematics Activities in the Workplace for Some Disciplines of Sewing and Fashion Design Technology Department at Technical Colleges in Saudi Arabia (The International Journal of Educational Sciences and Arts, 2023)
This research aims to reveal and understand mathematics activities in the workplace, for some disciplines of the Sewing and Fashion Design Technology Department at Technical Colleges in Saudi Arabia. The researchers used the qualitative research approach by designing an exploratory case study, to explore mathematics activities in the workplace through observing and interviewing a purposive sample of six participants from the market labour in the field of disciplines of sewing and fashion design technology. The findings of the research revealed six topics which are: describing mathematics in the workplace from the participants’ point of view, mathematics topics in the workplace, mathematics skills in the workplace, learning approaches in the workplace, working approaches in the workplace, and finally tools and techniques in the workplace. The research has included several recommendations, and the most highlighted one is for the curricula administration in the Technical and Vocational Training and Corporation to utilize the findings of this research in designing and constructing a mathematics course for sewing and fashion design technology department aligning with its vocational specializations, and labour market needs.
Keywords: Technical Colleges; Mathematics in the Workplace; Administrative Technology; Qualitative Research